How augmented reality affected academic achievement in K-12 education - a meta-analysis and thematic-analysis - Li, Feng; Wang, Xi; He, Xiaona; Cheng, Liang; Wang, Yiyu (Interactive learning environments, 2023)
The purpose of this study is to determine the effect of augmented reality (AR) applications on K-12 students' academic achievement through meta-analysis and thematic analysis. 40 samples from 35 articles published between 2006 and 2020 were used to examine the impact of AR on academic achievement and to explore the effects of differences in grade level, academic subject, duration of the experiment, and sampling methods. The research results showed that (1) AR has a medium effect on K-12 students' academic achievement (g = 0.437) according to the Thalheimer and Cook's effect size classification. (2) academic subject and duration of experiment as moderator variables have a significant influence on whether AR application will enhance K-12 students' academic achievement, and (3) the advantages of AR in K-12 education include enhancing interest and motivation, offering vivid resources, providing an interactive environment, and improving attention. The disadvantages include integrated method limitations, system function shortcomings, and the causing of physical discomfort problems. The advantages and disadvantages show why AR application has a medium effect on K-12 students' academic achievement.